Phylum Brachiopoda. In: Zhang, Z.-Q. (Ed.) Animal Biodiversity: An Outline of Higher-level Classification and Survey of Taxonomic Richness (Addenda 2013) - Emig, Christian C.; Bitner, Maria Aleksandra; Álvarez, Fernando (Zootaxa, 2013)
The number of living brachiopod genera and species recorded to date, are 116 and 391, respectively. The phylum Brachiopoda is divided into three subphyla: Linguliformea, Craniiformea and Rhynchonelliformea. Although they were extremely common throughout the Paleozoic, today they are considered a minor phylum, and only five orders have extant representatives: Lingulida, with two families, 6 genera and 25 species; Craniida, with one family, 3 genera and 18 species; Rhynchonellida, with 6 families, 19 genera and 39 species; Thecideida, with two families, 6 genera and 22 species; and Terebratulida, with 18 families, 82 genera, and 287 species.